The geology, petrology and controls on copper mineralisation in Exploration Prospecting Licence (EPL) 5836 along the matchless belt, Windhoek, Namibia - Ekandjo, Halleluya Naantu (My University, 2017)
The Kariam Prospect mineralisation is a quartz-carbonate vein hosted Cu (Mo-Au) deposit associated with quartz-carbonate schist and biotite-chlorite schist of the Kuiseb Formation in the Southern Zone or Khomas Trough of the Damara Orogen in Namibia. Geological mapping within the ‘Northern Part’ of the Kariam Prospect has identified two different types of schists which are different in composition and different in outcrop appearance, namely the fine-grained mica-rich and medium-grained quartz-rich schist. They dip shallowly between 15° - 55° towards 220° - 320° and strike ENE-WSW. They were originally sediments deposited around 630 Ma during the Neoproterozoic. Two different sets of veins have been noted around the schists reflecting different hydrothermal activities which have taken place in the area. The veins are i) Quartz-carbonate magnetic veins dipping steeply at 80° SE, estimated to have formed after deformation and ii) Quartz non-magnetic veins parallel to the schistosity with a steep dip inferred to have formed during deformation. A petrographic and borehole core investigation revealed that the different types of schists exhibit a different mineralogy attributed to alteration. Mineralisation in the form of chalcopyrite, pyrite, pyrrhotite and molybdenite occurs as disseminated ore, patches, blebs, and veinlets within the veins and matrix of the host rocks proximal to the mineralised veins. Adjacent alteration comprises proximal quartz-carbonate and early/distal biotite chlorite zoned clusters.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, February 2017.
Keywords: Geology, Stratigraphic